A COMPARATIVE STUDY ON THE PHYSICAL AND MECHANICAL PROPERTIES OF ALKALI ACTIVATED MATERIALS - Kabay, Nihat; Miyan, Nausad (YILDIZ TECHNICAL UNIV, 2020)
In this study, the effect of silica modulus (MS) on the properties of alkali activated material (AAM) was evaluated. The precursor material selected for the production of AAM was a blend of ground granulated blast furnace slag (GGBFS) and fly ash (FA). The activator was a mix of sodium hydroxide and sodium silicate having different silica modulus and constant Na2O dosage of 4% by mass of GGBFS and FA. The experimental study investigated the basic mechanical and physical properties of the mortars such as compressive strength, flexural strength, void ratio, water absorption, and density. Test results showed that the physical properties of the AAM mixes such as water absorption and voids content were higher compared to the OPC mix, however, the oven-dry density values were at similar levels, indicating that within the scope of this study at similar density, the AAM produces a more porous microstructure. The compressive strength of the AAM mix having silica modulus of 1.0 (AAM-1.0) was comparable to the OPC mortar at 3 and 7 days however at 28 days the OPC mix possessed significantly higher strength. The AAM mixes produced a lower flexural strength compared to the OPC mix at 28 days and the flexural to compressive strength ratio was almost halved in the AAM mixtures.
Keywords: Alkali activated material; ground granulated blast furnace slag; fly ash; silica modulus; physical properties; mechanical properties; DRYING SHRINKAGE; STRENGTH; GEOPOLYMER; BEHAVIOR; CEMENT; FRESH; Engineering